Contribuição metodológica para a elaboração do diagnóstico físico-conservacionista (DFC) em bacias hidrográficas: aplicação na Bacia do Alto Gurguéia, Piauí (Brasil) - Morais, Reurysson Chagas de Sousa (2018)
The uncontrolled occupation and the intensive use of natural resources are potential environmental degradation factors in watersheds. Acknowledging the environmental potentialities and limitations of a basin from the integrated analysis of its natural setting is an important tool of environmental management. Classical methodologies of environmental diagnosis, such as the Physical-Conservationist Diagnosis (PCD), fail as they don’t consider the relative influence of each analysis parameter of the physical degradation condition of a basin. Thus, the purpose of this study is to present a methodological contribution to the PCD elaboration of watersheds from the use of data stemming from remote sensing, fuzzy-logicbased special modelling and multiple criteria analysis method (Analytic Hierarchy Process – AHP). For this purpose, seven environmental parameters were selected: vegetal covering index, soil protection index, terrain inclination, drainage density, rain erosivity, climatic index and soil erosivity. The effectiveness of the proposed methodology was evaluated in the Bacia Hidrográfica do Alto Gurguéia (BHAG) located at the far south of the state of Piauí, Brazil. The results indicate that the BHAG presents very low to very high risk of physical degradation. The very high risk areas are related to the incidence of steep slope and exposed soil, while the areas with very low physical degradation risk are at the top of tablelands and plateaus covered with arboreal and dense shrub (Cerrado) vegetation. Among the medium risk areas are those located near the drainage headwaters of the Gurguéia river that although presenting preserved vegetation, those are zones with high potential of physical degradation due to the natural weakness of the soil. An environmental zoning of the BHAG based on the PCD was drawn up in order to demonstrate that. Therefore, five zones that reflect the various geoenvironmental conditions and the categories of the land use were defined. The Areas of High Degradation Risk comprise 44% of the basin area, while the Restricted Use Areas, Potentially Productive Areas and Productive Areas cover respectively, 18%, 14% and 18% of the total area. The Protected Areas are only 6% of the basin. In the context of the application made, the information about the physical degradation of the BHAG related to the environmental zoning proposal is expected to, initially, warn about the risks of decaying that the BHAG is exposed, define priority areas of preservation and assist with the process of environmental and water resources management. It is believed that the methodological proposal developed in this research represents an improvement in obtaining the PCD of water basins by incorporating new analysis methods, thus allowing a specialized assessment of the physical degradation risk. Whereas the maintenance of a database in a Geographic Information System (GIS) environment may aid in the environmental planning by enabling constant updating of the environmental data, assuring quickness and accuracy on the access to the information.